‘Our Care through our Eyes’: a mixed methods,evaluative study of a service user,co-produced education programme to improve inpatient care of children and young people admitted following self-harm - Manning, Joseph. C.; Latif, Asam; Carter, Tim; Cooper, Joanne; Horsley, Angela; Armstrong, Marie; Wharrad, Heather (BMJ Publishing Group, 2015)
Introduction: Within Europe, the UK has one of the highest rates of self-harm, with a particularly high prevalence in children and young people (CYP). CYP who are admitted to paediatric hospital wards with self-harm are cared for by registered children's nurses who have been identified to lack specific training in caring for this patient group. This may impede the delivery of high quality care. Therefore, this study aims to co-produce, implement and evaluate an education programme for registered children's nurses to improve their knowledge, attitudes and confidence when caring for CYP admitted with self-harm.